The Contribution of Green Finance to Achieving Sustainable Development - Nikolic-Ristic, Dragana; Marković, Ivana (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
The pronounced trend of transition to reduced use of fossil fuels, on the one hand, and greater use of renewable energy sources, on the other hand, leads to putting the concept of sustainable economy in the focus of interest of the scientific and professional public. In this context, the paper presents the importance of sustainable development, which implies the existence of an adequate balance between meeting the basic needs of people and ensuring an adequate standard of living with the rational use of natural resources and environmental protection. After defining sustainable development, the importance and need to create green financing strategies with the aim of achieving sustainable development is pointed out. Taking into account the importance of green financing in the transition to a green economy, it is possible to identify several projects from the European Union and the region that aim to finance renewable energy projects through credit lines of commercial banks for green financing. The purpose of this paper is to present the current state of green finance in domestic conditions, and the aim of the paper is to consider the contribution of green finance to achieving sustainable development. The conclusion of the paper emphasizes the need for continuous development of green financing projects and a more active role of both state institutions and commercial banks.